Cooperative Capture of Uranyl Ions by a Carbonyl‐Bearing Hierarchical‐Porous Cu–Organic Framework - Wang, Xiao‐Feng; Chen, Yangyang; Song, Li‐Ping; Fang, Zhen; Zhang, Jian; Shi, Fanian; Lin, Ying‐Wu; Sun, Yunkai; Zhang, Yue‐Biao; Rocha, João (Angewandte Chemie International Edition, 2019)
To efficiently capture the toxic uranyl ions (UO22+), a new hierarchical micro‐macroporous metal–organic framework was prepared under template‐free conditions, featuring interconnected multi‐nanocages bearing carbonyl groups derived from a semi‐rigid ligand. The material exhibits an unusually high UO22+ sorption capacity of 562 mg g−1, which occurs in an intriguing two‐steps process, on the macropore‐based crystal surface and in the inner nanocages. Notably, the latter is attributed to the cooperative interplay of the shrinkage of the host porous framework induced by uranyl accommodation and the free carbonyl coordination sites, as shown by both single‐crystal X‐ray diffraction and a red‐shift of the infrared [O=UVI=O]2+ antisymmetric vibration band. Uranyl capture: A hierarchical micro/macroporous copper metal–organic framework featuring carbonyl‐group‐decorated multi‐nanocages shows one of the highest uranyl cation saturation sorption capacities, 562 mg g−1, as determined by a two‐step adsorption process.